The performance evaluation of NIPT for fetal chromosome microdeletion/microduplication detection: a retrospective analysis of 68,588 Chinese cases - Shen, Shichun; Qi, Haimei; Yuan, Xianping; Gan, Jinhui; Chen, Junkun; Huang, Jungao (Frontiers in Genetics, 2024)
Background: Chromosomal abnormalities are the main cause of birth defects in newborns. Since the inception of noninvasive prenatal testing (NIPT) technology, it has primarily been applied to the detection of common trisomy (T21, T18, T13). However, the application of NIPT in microdeletion and microduplication detection is still controversial. Methods: This study retrospectively analyzed the data of 68,588 cases that underwent NIPT at Ganzhou Maternal and Child Health Hospital in China. These data were used to evaluate the performance of NIPT in fetal chromosome microdeletion/microduplication detection and to investigate the key factors affecting the NIPT performance. Results: A total of 281 cases (0.41%) had positive NIPT results with copy number variants (CNVs), of which 161 were validated by karyotyping and chromosome microarray analysis (CMA). Among the 161 cases, 92 were confirmed as true positives through karyotyping or CMA, including 61 microdeletion cases and 31 microduplication cases, resulting in a positive predictive value (PPV) of 57.14 %. Improvements in library construction methods increased the fraction of cell-free fetal DNA (cffDNA) from 13.76% to 18.44%, leading to a significant improvement in the detection rate (0.47% vs 0.15%) and PPV (59.86% vs 28.57%) of NIPT for CNVs.This study proved the robust performance of NIPT for fetal chromosome microdeletion/microduplication detection. In addition, the cffDNA fraction is a key factor influencing NIPT, with increased cffDNA fraction improving the performance of NIPT.